Analysis of Community Sentiment Towards Service and Accommodation Quality in Labuan Bajo Using Support Vector Machine - Ni Wayan Anggita Dara Pratiwi; I Dewa Putu Gede Wiyata Putra; Ida Kurniawati; Made Dona Wahyu Aristana (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Labuan Bajo is one of the government's priority destinations. Although the Tourism Government prioritizes Labuan Bajo as a new 10 Bali destination with the aim of attracting world tourists, until now the number of visitors to Labuan Bajo is still lower than Bali. The research method involves several stages, data collection through data crawling, data labeling, data preprocessing, data sharing, classification with Support Vector Machine method, and model evaluation. The results show that negative sentiment dominates with a percentage of 53%, while positive sentiment is 46% and is supported by the results of testing using confusion matrix to determine the accuracy of the support vector machine algorithm, which gets 82% accuracy, then positive class precision of 82%, negative class precision of 83% and positive class recall of 80%, and negative class recall of 84%.